O jogo pedagógico enquanto atividade orientadora de ensino na iniciação algébrica de estudantes de 6ª série - Gaspar, Regiane de Oliveira (2013)
This research is conducted by the following question: what are the mathematics learning that students from the 6th grade when explicit activities guiding experience teaching algebra mediated by an educational game? Thus, we proposed Guiding Teaching Activities (Moura, 2001) to thirty-one students of the sixth grade of the state of the city of Araraquara in 2012. The lessons were videotaped and analyzed. Proposed activities involving games where students could continually revise their way of solving a problem situation, while they acquired a new language of mathematics: algebraic. To better understand the knowledge expressed in the speeches of the students studied the contributions of the game as teaching methodology, as well as the common difficulties that students have when they start in algebra. From the analysis of the episodes concluded that, for most students who have contact with pictorial and numerical sequences, such understanding does not occur naturally, much less its generalization. It was also evident that students on contact, for the first time, with the algebraic symbolization not view it as something practical. Prefer to use rhetorical language to solve problem situations involving equations.